Lignocellulose biomass pyrolysis for bio-oil production: A review of biomass pre-treatment methods for production of drop-in fuels. (May 2020) - Kumar, R.; Strezov, V.; Weldekidan, H.; He, J.; Singh, S.; Kan, T.; Dastjerdi, B.
Abstract: Bio-oil upgrading can be achieved mainly via three types of methods that are biomass pre-treatment, catalytic upgrading and downstream bio-oil upgrading. The article aim is to review the different physicochemical biomass pre-treatment methods used to improve the physiochemical properties of the bio-oils produced from pyrolysis of treated biomass. Biomass pre-treatment could be classified as physical, thermal, chemical and biological methods. The physical methods, such as grinding and densification improve the biomass particle size and density, affecting the heat flow and mass transfer during pyrolysis, while thermal methods, such as torrefaction, decrease the activation energy of the pyrolysis process and increase the amount of hydrocarbons in the produced bio-oil. The chemical methods generally remove the minerals and alkali metals from the biomass, improve its calorific value and enhance other biomass properties. The biomass pre-treatment methods can be integrated with catalytic pyrolysis to enhance the total carbon yield and aromatic hydrocarbons in the bio-oil. This article provides review of the basic principles of the methods, important parameters that affect biomass properties, highlights the key challenges involved in each treatment method and suggests possible future recommendations to further understand the influence of the pre-treatment methods on bio-oil upgrading. In the last section, the effect of integrated catalytic pyrolysis and pre-treatment methods on bio-oil upgrading is provided. Highlights: Biomass pre-treatment methods for bio-oil upgrading are thoroughly discussed. Basic principles and key advantages of all the methods are highlighted. Thermal methods improve the biomass structure and energy content. Chemical treatments remove undesirable inorganic species from the biomass. Catalytic pyrolysis with pre-treated biomass increases aromatics in the bio-oil.